Social dialogue in times of global economic crisis - Triomphe, Claude-Emmanuel; Guyet, Rachel; Tarren, David (Luxembourg, 2012)
"Social dialogue is one of the cornerstones of social Europe and involves employers, workers and their representatives, and, in tripartite structures, also public authorities in the discussions and negotiations which shape social policy and industrial relations. This study seeks to establish how far Member States were willing or able to use social dialogue as a tool to mitigate the effects of the financial downturn in the wake of the profound global economic crisis which began in autumn 2008. It analyses where it was used, how effective it was and also identifies the factors that could make it more or less likely that the social partners would be involved in efforts to respond to the crisis."